Evidence against attentional state modulating scalp-recorded auditory brainstem steady-state responses - Varghese, Leonard (Brain Res, 2015)
Auditory brainstem responses (ABRs) and their steady-state counterpart (subcortical steady-state responses, SSSRs) are generally thought to be insensitive to cognitive demands. However, a handful of studies report that SSSRs are modulated depending on the subject’s focus of attention, either towards or away from an auditory stimulus. Here, we explored whether attentional focus affects the envelope-following response (EFR), which is a particular kind of SSSR, and if so, whether the effects are specific to which sound elements in a sound mixture a subject is attending (selective auditory attentional modulation), specific to attended sensory input (inter-modal attentional modulation), or insensitive to attentional focus. We compared the strength of EFR-stimulus phase locking in human listeners under various tasks: listening to a monaural stimulus, selectively attending to a particular ear during dichotic stimulus presentation, and attending to visual stimuli while ignoring dichotic auditory inputs. We observed no systematic changes in the EFR across experimental manipulations, even though cortical EEG revealed attention-related modulations of alpha activity during the task. We conclude that attentional effects, if any, on human subcortical representation of sounds cannot be observed robustly using EFRs.